2020
DOI: 10.3390/ma13102305
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Space Trusses Using Spacers of Concrete with Steel Fiber and Sisal Fiber

Abstract: Space trusses are structural systems, generally made of tubes, used worldwide because of their advantages in covering long-span roofs. In addition to having a low cost, the truss weight is relatively reduced. The load capacity of these structures depends also on the strength of their node connection. Connections made with the superposition of flattened tube ends trespassed by one bolt are, generally, known as typical nodes. They are inexpensive but present eccentricities that reduce significantly the strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Space trusses are made from different materials such as steel, aluminum, wood etc. Space trusses were copied from nature, the natural elements always seek to minimize stress and maximize strength in an efficient way, taking advantage of the load capacity of all members of the body [1, 3,4]. The natural shapes have exceptional stiffness and use minimum materials to obtain the maximum structural advantage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Space trusses are made from different materials such as steel, aluminum, wood etc. Space trusses were copied from nature, the natural elements always seek to minimize stress and maximize strength in an efficient way, taking advantage of the load capacity of all members of the body [1, 3,4]. The natural shapes have exceptional stiffness and use minimum materials to obtain the maximum structural advantage.…”
Section: Introductionmentioning
confidence: 99%
“…There are high concentrations of stress on the nodal region, separation and slip between bars, which can sensibly increase the loss of bearing capacity with the emergence of bending moment [4,11,16]. (c) The eccentricities in the connections can cause increases of stress for a reduced nodal stiffness [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A space truss type that has been frequently adopted as a structural system worldwide is the one composed of hollow circular cross-section bars, whose ends are previously flattened to promote coupling with other connection members by use of a single bolt. According to Bezerra et al and Silva et al [1][2], the simplicity and low cost of its construction method are relevant factors in its choice among engineering professionals. Despite this fact, some of its critical features, such as potential bending moments generated by eccentricity in the connections and the reduced rigidity due to the flattening process, must be duly considered in the designing process Silva et al [3].…”
Section: Introductionmentioning
confidence: 99%
“…Already in 2013, another failure of a coverage in space truss using bar with reduced section in conical shape occurred in the Shah Alam Stadium football at Malaysia. The report carried out by the Malaysia technical team concluded that the collapse was due to buckling of the bars and in conjunction with the rupture of several connections [2,[20][21]. In this context, the Fig.…”
Section: Introductionmentioning
confidence: 99%